A systematic review that evaluates the extent and quality of involving childhood abuse survivors in shaping, conducting and disseminating research in the UK. (27th January 2022) - Kennedy, Simone; Bewley, Susan; Chevous, Jane; Perôt, Concetta; Vigneri, Marcella; Bacchus, Loraine J.
Abstract : page_1 other Despite a well-established understanding of the mental and physical health consequences associated with exposure to childhood abuse, the active voices of survivors are rarely present in shaping, conducting and disseminating research. To explore the extent and quality of involvement with adult survivors of childhood abuse in the UK, we performed a systematic review of research conducted 'with' or 'by' survivors, and analysed involvement against a new instrument, the Survivor Research Involvement Ladder, which was co-produced drawing from the principles of the Survivors Voices Charter. A search of relevant grey and peer-reviewed literature was conducted, which retrieved 662 sources after removing duplicates. Of these, 116 full-text articles on adult survivors of childhood abuse in the UK were subsequently assessed for involvement (beyond participation as 'subjects'), of which page_2 other only 15 (12.9 per cent) reported activities led, co-produced, advised or consulted on by survivors, and these were included in the review. From evaluations and analysis using the ladder, consumerist models were found to be the dominant form of involvement, with survivors filling advisory roles at isolated stages. Survivor-led research was scarce but emerged when survivor-researchers planned, conducted and disseminated their work. This review finds considerable opportunity for improvements in the level, quality and subsequent reporting of research activities involving survivors. The use of the instrument needs replication, validation and further field-testing.